PENINGKATAN PRODUKTIVITAS DAN MANAJEMEN UD. MJ FASHION MELALUI PENERAPAN MESIN PRESS SEPATU DAN OVEN PENGERING OTOMATIS - Yunus; Arifiana, Deny; Prakoso, Albrian Fiky; Pambudi, Rizdana Galih; Anshari, Bima (Universitas Negeri Surabaya, 2025)
SMEs have a major impact in improving the welfare of society through their contribution in moving the wheels of the economy in social life. One example is UD. MJ Fashion Sidoarjo, an SME engaged in conventional shoe craftsmen. However, through the results of interviews and situation analysis with partners, several problems were found including the low quality and quantity of production due to uneven drying results on the entire surface of the sole and upper shoes which have an impact on the low quality and quantity of products that affect the growth of UD's business. MJ Fashion Sidoarjo, causing slow productivity which results in a decrease in competitiveness and loss of customers. As a solution to overcome these problems, the PKM Team conducted a method of direct application of the use of Shoe Press Machines and Automatic Drying Ovens. With the hope of providing a solution to the problem of quality and quantity of shoe production. With the machine, it is anticipated that there will be a significant increase in the aspects of Quality Management and Productivity in the shoe production process while increasing the operational efficiency of UD. MJ Fashion Sidoarjo, but also has the potential to make a positive contribution to the local economy and community welfare through increased competitiveness and business growth.